The Sartre Dictionary. - Cox, Gary (Continuum philosophy dictionaries., 2008)
[This book] offers lucid and thorough explications of key Sartrean concepts and even phrases, and it contains revealing accounts of the numerous thinkers and writers who influenced Sartre ... This book will open doors. David Pugmire, Department of Philosophy, University of Southampton, UK The Sartre Dictionary is a comprehensive and accessible guide to the world of Jean- Paul Sartre. Meticulously researched and extensively cross-referenced, this unique book covers all of his major works, ideas and influences and provides a firm grounding in the central themes of Sartre''s thought. Students.